Exhaustivity, contrastivity, and the semantics of Mandarin cleft-related structures - Liu, Ying (Researcher in linguistics) (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"Exhaustivity, Contrastivity, and the Semantics of Mandarin Cleft-related Structures investigates the semantics of the cleft and cleft-related structures in Mandarin, which, over several decades, have presented analytical challenges for semantic theory. The goal of this book, in broad terms, is three-fold: (i) to figure out what clefting adds to the semantics of a sentence; (ii) to set apart the meaning and the discourse function of each type of cleft-related structure; and (iii) to provide a uniform analysis of Mandarin clefts and their related structures. More specifically, it addresses the following questions: (i) what is the semantics of Mandarin clefts? (ii) what do exhaustivity and contrastivity contribute to the meaning of clefts? (iii) what are the semantic (or pragmatic) factors that determine the variation of clefts, related structures, and canonical sentences? and (iv) cross-linguistically speaking, how do Mandarin shi...de cleft and its related structures differ from similar constructions such as English it-cleft, French c'est cleft, and German es-cleft? This book will be informative for linguists who are working on cleft constructions, focus sensitive structures cross-linguistically, and those interested in experimental semantics and pragmatics"--
Theoretical background -- Clefts and the related structures -- The interpretation of clefts -- A unified analysis of shi-clefts -- The semantics of de.
Keywords: Chinese language -- Semantics; Comparative linguistics; FOREIGN LANGUAGE STUDY / General; FOREIGN LANGUAGE STUDY / Chinese